Photodynamic therapy in treatment of trophic ulcers in patients, suffering chronic venous insufficiency - Yu. V. Іvanova; S. M. Gramatyuk; І. A. Kryvoruchko; O. O. Zarudnyi; K. V. Miasoiedov (Клінічна хірургія)
Objective. Elaboration of complex approach to treatment of trophic ulcers of venous etiology, using photodynamical tissue therapy and modern types of the wound coverage.